AKIBAT HUKUM KUASA MUTLAK DALAM AKTA PENGIKATAN JUAL BELI DENGAN PEMBAYARAN PENUH ATAS OBJEK JUAL BELI - Harpami, Yaumal Akmal; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The sale and purchase agreement is a legal breakthrough from thecomplexity of fulfilling all the requirements related to the sale and purchasebefore a notary public. Even though the contents have already regulated the saleand purchase of land, the format is only limited to sale and purchase agreement,namely a form of agreement which constitutes or can be said to be a preliminaryagreement. However, the contents of the sale and purchase agreement contain anirrevocable power called absolute power, which has been regulated in theInstruction of the Minister of Home Affairs Number 14 of 1982 concerning theProhibition of Using Absolute Power as Transfer of Rights to Land. The purposeof this study was to determine the legal consequences of absolute power in thesale and purchase agreement deed with full payment.The type of research that the author uses in this research is normativeresearch, the writer uses this type of research on the level of synchronization, isthe extent to which the existing written positive laws are synchronous orcompatible with each other based on the applicable laws and prioritizing librarymaterials. The conclusion of this research is that the use of irrevocable power ofattorney is intended to provide legal certainty to buyers who have paid in full theobject of sale and purchase according to the price stated in the sale and purchaseagreement deed and are not proxies prohibited by Instruction of the Minister ofHome Affairs No. 1982 concerning the Prohibition of Using Absolute Power asTransfer of Rights to Land. So that the legal status is legal to do for the purpose ofprotecting the interests of buyers who have paid for the object of sale andpurchase. Protection of the rights of the parties if one of the parties defaults in thesale and purchase agreement, the protection is in accordance with the protectionof the authentic deed because the sale and purchase agreement deed made is anotary deed drawn up by or before a notary public.Key words: Deed - Sale and Purchase Agreement - Absolute Authority